The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3205/zma001533
|View full text |Cite
|
Sign up to set email alerts
|

Everybody is able to reflect, or aren't they? Evaluating the development of medical professionalism via a longitudinal portfolio mentoring program from a student perspective

Abstract: Introduction: Reflective competence is fundamental for responsible medical practice and must be systematically incorporated in medical training. To promote this, a longitudinal portfolio-based mentoring program was made mandatory at the Medical Faculty of the University of Tübingen in 2013. This study examines medical students' attitudes toward professional reflection and toward the program in general to draw conclusions about conditions as well as the needs-based design of the program. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 39 publications
(69 reference statements)
0
3
0
Order By: Relevance
“…For example, Davis et al [15] and Salah ElDin et al [17] found that while some students appreciated the opportunity for self-reflection and showcasing their work through portfolios, others expressed concerns about the time and effort required to compile and maintain them. Similarly, Schrempf et al [30] and Salah ElDin et al [17] reported that students valued the authentic assessment opportunities provided by portfolios but struggled with understanding the assessment criteria and expectations.…”
Section: Students' Perceptions Towards Portfolio Assessment Practicesmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Davis et al [15] and Salah ElDin et al [17] found that while some students appreciated the opportunity for self-reflection and showcasing their work through portfolios, others expressed concerns about the time and effort required to compile and maintain them. Similarly, Schrempf et al [30] and Salah ElDin et al [17] reported that students valued the authentic assessment opportunities provided by portfolios but struggled with understanding the assessment criteria and expectations.…”
Section: Students' Perceptions Towards Portfolio Assessment Practicesmentioning
confidence: 99%
“…Students' attitudes toward portfolio assessment practices play a crucial role in their acceptance and engagement. Research by Nungari [11], Suwaed [13], and Schrempf et al [30] demonstrated that students' positive attitudes toward portfolio assessment were associated with higher levels of motivation and commitment to learning. Conversely, students with negative attitudes may resist or disengage from the assessment process, impacting the validity and reliability of the assessment outcomes [30].…”
Section: Students' Attitudes Towards Portfolio Assessment Practicesmentioning
confidence: 99%
“…This issue discusses a number of topics that may deserve a place in teacher training programs. Schrempf et al [ 10 ] describe the relevance of mentoring and guiding students in reflecting on their competence development. It may also be relevant if teachers recognise when students are using intuitive concepts, as described in the article by Harendza & Herzog [ 11 ].…”
Section: Editorialmentioning
confidence: 99%
“…In view of the current National Competence-Based Learning Objectives Catalogue (NKLM), describing competencies and learning objectives as a guideline for German faculties and therewith for curriculum development, competency-based medical education (CBME) has become a main approach in medical education and teaching methods [ 14 , 15 ]. Because self-reflection is described within the NKLM as an integrative part of the medical curricula, recently, Schrempf et al presented approaches concerning how to integrate this fundamental and important tool within the educational practice [ 16 ].…”
Section: Introductionmentioning
confidence: 99%